Jurnal TINJAUAN YURIDIS PELAKU TINDAK PIDANA INCEST TERHADAP ANAK DIBAWAH UMUR DI POLEWALI MANDAR : PELAKU TINDAK PIDANA INCEST - Jalil B. (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Institut Agama Islam Negeri Sultan Amai Gorontalo, 2022)
This study aims to analyze cases of incest crimes against minors with the problem of causal factors and the impact of incest on community life. This research is field research located in Polewali Mandar Regency with primary data sources from the District Court of Polewali Mandar Regency Case Decision Number: 68/Pid.Sus/2020/PN-Pol. While secondary data sources are books, journals, and legislation related to the problem. The data collected was analyzed with descriptive qualitative with a normative juridical approach. The results showed that in handling incest cases against minors, they were prosecuted under Article 294 paragraph (1) of the Criminal Code and Article 295 paragraph (1) item (1) of the Criminal Code. Factors causing incest against minors are caused by internal factors and external factors. Meanwhile, the consequences have short-term and long-term impacts on child victims of incest.